The Influence of Accountability And Transparency on The Management of The Apbesa of Tumbang Bunut Village, Rungan District, Gunung Mas Regency - SELVIANI NINGSIH; RAHMIATI RAHMIATI; M.ICHSAN DIARSYAD (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2019)
The porpose of this study is to determine the readiness of village government in realizing accountability and transparency in the management of APBDesa By quantitative method there hypotheses proposed in this study. The subjects of this research are 4 principal areas of village, village government of Tumbang Bunut, The sampling technique in this research is done using the techningque of vorposive sampling the instrument of data collection in this research is questionnaire of questionnaire. The resuls of this study indclate that accountability is positively releated to the management of APBDesa, Transparency is also positively realited to the management of APBDesa, and accountability, and transparency together have a positive relationship to APBDesa Mangement